Sustained reperfusion after blockade of glycoprotein-receptor-Ib in focal cerebral ischemia: an MRI study at 17.6 Tesla - Pham, Mirko; Helluy, Xavier; Kleinschnitz, Christoph; Kraft, Peter; Bartsch, Andreas J.; Jakob, Peter; Nieswandt, Bernhard; Bendszus, Martin; Stoll, Guido (PLOS ONE, 2011)
BACKGROUND: Inhibition of early platelet adhesion by blockade of glycoprotein-IB (GPIb) protects mice from ischemic stroke. To elucidate underlying mechanisms in-vivo, infarct development was followed by ultra-high field MRI at 17.6 Tesla. - METHODS: Cerebral infarction was induced by transient-middle-cerebral-artery-occlusion (tMCAO) for 1 hour in C57/BL6 control mice (N=10) and mice treated with 100 µg Fab-fragments of the GPIb blocking antibody p0p/B 1 h after tMCAO (N=10). To control for the effect of reperfusion, additional mice underwent permanent occlusion and received anti-GPIb treatment (N=6; pMCAO) or remained without treatment (N=3; pMCAO). MRI 2 h and 24 h after MCAO measured cerebral-blood-flow (CBF) by continuous arterial-spin labelling, the apparent-diffusion-coefficient (ADC), quantitative-T2 and T2-weighted imaging. All images were registered to a standard mouse brain MRI atlas and statistically analysed voxel-wise, and by cortico-subcortical ROI analysis. - RESULTS: Anti-GPIb treatment led to a relative increase of postischemic CBF vs. controls in the cortical territory of the MCA (2 h: 44.2±6.9 ml/100 g/min versus 24 h: 60.5±8.4; p=0.0012, F((1,18))=14.63) after tMCAO. Subcortical CBF 2 h after tMCAO was higher in anti-GPIb treated animals (45.3±5.9 vs. controls: 33.6±4.3; p=0.04). In both regions, CBF findings were clearly related to a lower probability of infarction (Cortex/Subcortex of treated group: 35%/65% vs. controls: 95%/100%) and improved quantitative-T2 and ADC. After pMCAO, anti-GPIb treated mice developed similar infarcts preceded by severe irreversible hypoperfusion as controls after tMCAO indicating dependency of stroke protection on reperfusion. - CONCLUSION: Blockade of platelet adhesion by anti-GPIb-Fab-fragments results in substantially improved CBF early during reperfusion. This finding was in exact spatial correspondence with the prevention of cerebral infarction and indicates in-vivo an increased patency of the microcirculation. Thus, progression of infarction during early ischemia and reperfusion can be mitigated by anti-platelet treatment.